Type specimens of Heteroptera (Insecta: Hemiptera) collected from North Korea and adjacent regions deposited at Insect Collections of Chungnam National University (CNU) in Daejeon, Republic of Korea - Jung, Sunghoon; Kim, Junggon; Oh, Sumin; Heiss, Ernst (Zootaxa, 2015)
A list of type specimens of Heteroptera (Insecta: Hemiptera) collected from North Korea (mostly by the late Dr. Michail Josifov, Sofia, Bulgaria) acquired earlier by E. Heiss, now donated to and deposited in the insect collections of Chungnam National University (CNU), Deajeon, Korea, is presented. A total of 31 holotypes and 694 paratypes of 41 species and 1 subspecies in 6 families and 9 subfamilies are presented: Miridae (Deraeocorinae, Mirinae, Orthotylinae, Phylinae), Tingidae (Tinginae), Piesmatidae (Piesmatinae), Berytidae (Metacanthinae), Cymidae (Cyminae), Pentatomidae (Asopinae).